2019
DOI: 10.3390/resources8030149
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Renewable Energy Resources Using Remote Sensing and GIS—A Review

Abstract: Renewable energy has received noteworthy attention during the last few decades. This is partly due to the fact that fossil fuels are depleting and the need for energy is soaring because of the growing population of the world. This paper attempts to provide an idea of what is being done by researchers in remote sensing and geographical information system (GIS) field for exploring the renewable energy resources in order to get to a more sustainable future. Several studies related to renewable energy resources vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 68 publications
0
35
0
Order By: Relevance
“…This manual process is not only time consuming and expensive, but also not suitable for analysis over a regional scale ( Duan et al, 2013 ; Ritchie et al, 2003 ). Recently, remote sensing techniques have been widely used to undertake these studies with accuracy, and advantageous of having both cost and time over the manual approaches ( Yunus et al, 2019 ; Avtar et al, 2019 ). The use of remotely sensed data helps not only to monitor and identify the water quality over large regions, but temporal changes can also be assessed regularly.…”
Section: Introductionmentioning
confidence: 99%
“…This manual process is not only time consuming and expensive, but also not suitable for analysis over a regional scale ( Duan et al, 2013 ; Ritchie et al, 2003 ). Recently, remote sensing techniques have been widely used to undertake these studies with accuracy, and advantageous of having both cost and time over the manual approaches ( Yunus et al, 2019 ; Avtar et al, 2019 ). The use of remotely sensed data helps not only to monitor and identify the water quality over large regions, but temporal changes can also be assessed regularly.…”
Section: Introductionmentioning
confidence: 99%
“…As Asia and Africa currently house 90% of the world's rural population, they are urbanizing faster than any other region and are predicted to achieve urbanization rates of 56% and 64%, respectively, by 2050 [4]. The rise in urban population is expected to be high in India, China, and Nigeria, where 35% of the world urban population growth is predicted to occur during 2018-2050 [5,6]. Urbanization brings a number of benefits to the Asian countries [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The possible impact of dams on the river flow regimes across the world varies based on the terrain, topography, ecology, and socioeconomic conditions of the region. In the climate change scenarios and impact of global warming, estimated runoff contributions to the total runoff from snow and glacier melt in the Beas at 35%, the Chenab 49%, and the Satluj 60% at present are going to increase with the increase in snow and glaciers melting [46][47][48]. Ali et al [8] suggested the wetter 17.04 ± 20.76% and 15.30 ± 20.16% increase in the annual mean precipitation in the Nathpa Jhakri (1500 MW) and Bhakra Nangal (1300 MW) big storage dams of the Satluj basin, respectively, in the near future was owing to snow and glaciers melting.…”
Section: Discussionmentioning
confidence: 99%